Degradation of sertraline using a continuous-flow filtration/photocatalysis system based on carbon fiber (PWB-3) modified with WO3 under LED chip irradiation - Rojas-Mantilla, Hernán Dario [UNESP]; Irikura, Kallyni [UNESP]; de Souza, João Carlos [UNESP]; Ayala-Durán, Saidy Cristina [UNESP]; Lima Gomes, Paulo Clairmont Feitosa de [UNESP]; Salazar-González, Ricardo; Boldrin Zanoni, Maria Valnice [UNESP] (Elsevier, 2023)
This work describes a filtration/photocatalytic system based on carbon fiber (CF) PWB-3 modified with WO3, to obtain a system capable of simultaneously filtering and degrading sertraline (SER) in simulated and real effluents. The CF was prepared by chemical electrodeposition and subsequent thermal treatment at 450 °C. X-ray diffraction patterns of CF/WO3/450 showed characteristic peaks for C and WO3 in monoclinic phase (more photoactive). The material presented broad absorption in UV–Vis range (300–700 nm), and a band gap of 3.6 eV. Scanning electron micrographs showed a thin film (WO3) formation on the CF surface. XPS analysis assigned the species C 1s, O 1s, W (4f, 4f7/2, 4d5/2 4d3/2), in addition to an intense peak at 530 eV attributed to metallic bonding (W-O). Modification with WO3 increased BET surface area from 0.20 to 3.1 m2 g−1, indicative of mesoporous-type material. Evaluation of the filtration/photocatalysis system under experimental conditions (100 mL, 2.0 mg L-1 SER, pH 5.6, and UV LED irradiation) enabled the optimization of reactor operating parameters. Use of an ideal flow rate of 180 mL min−1 and a membrane stabilization time of 30 min provided adequate contact between the solid and liquid phases and good mass transfer, achieving concentrations below the limit of detection for simulated and real effluent samples, at 90 and 30 min, respectively. It was shown that HO•, 1O2, O2•-, H2O2, and h+ played an important role in SER degradation, with some degradation products being identified and the main route being hydroxylation, demethylation, and dechlorination reactions. The combined system showed excellent potential for filtration applications, reducing problems associated with encrustation, providing rapid retention, and simplifying the treatment of contaminated water.
Keywords: Antidepressant; Hybrid systems; LED irradiation; Membrane; Semiconductor